Bimbingan Teknis Penentuan Harga Jual Pada Usaha Konveksi ALFAZ Di Kelurahan Kambu Kota Kendari - Teguh Permana; Andriani Puspitaningsih; Surianti; Eka Safitri Paijum (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The results of community service indicate that ALFAZ business owners are enthusiastic about following the material provided which begins with providing ALFAZ business owners understanding about business management which consists of funding and working model turnover and business innovation. The next activity is to provide an understanding of the types of costs, both fixed costs and variable costs. After that increase the technical ability to determine the price and calculate the BEP. ALFAZ business owners have not been able to fully determine pricing because it is considered complicated to calculate fixed costs, especially the depreciation cost component. Because so far the manager determines the price from the standard price among competitors, the level of complexity of the stitches and the available stock of raw materials.